Consideration for eliminating conjunctival closure in the enucleation procedure. (3rd September 2017) - Pemberton, John D.; Wright, Hugh; Fowler, Brian T.; Kim, Juliet; Fleming, James C.
ABSTRACT: To compare post-operative results and complications in patients who undergo enucleation with or without suture closure of the conjunctiva. This was a retrospective chart review study. Review of 50 cases of enucleation surgery at the University of Arkansas for Medical Sciences and Arkansas Children's Hospital between July 2011 and December 2014. Criteria for inclusion in the study were all cases of enucleation that had extraocular muscles attached to a spherical orbital implant with or without conjunctival closure, and at least 2 months of postoperative follow up. Post-operative complications were evaluated. A total of 36 cases fulfilled the criteria for inclusion in the study; 12 cases with direct sutured layered direct closure of Tenon's and then conjunctiva and 24 cases with Tenon's capsule sutured closure but without direct conjunctival sutured closure. No implant complications were identified in either group (p = 1.0). Mean follow-up for all groups was 16.71 months (range 2 to 43 mo., SD 11.94). Mean follow up for the non-closure group was 14.42 months (range 2.25 to 36 mo., SD 10.35). Two cases in the conjunctival closure group developed a conjunctival cyst, affecting prosthesis fit, approximately 3 months postoperatively: no such cysts were identified in the non-conjunctival closure group. Fisher exact test for cyst formation between the two groups was not statistically significant (p = 0.1048). Direct conjunctival closure following enucleation surgery does not appear to increase the risk of extrusion, exposure, or infection. Foregoing direct closure decreases surgical time and reduces cost. It is unclear if this decreases conjunctival cyst formation.